Peran Komitmen Organisasional Sebagai Mediator Pengaruh Keadilan Prosedural dan Kepuasan Kerja Terhadap Organizational Citizenship Behaviour Karyawan PT Patrari Jaya Utama - Sumijan Sumijan (INOBIS: Jurnal Inovasi Bisnis dan Manajemen Indonesia, 2021)
The purpose of this study was to examine and analyze the effect of Procedural Justice and Job Satisfaction on Organizational Commitment; to examine and analyze the effect of Procedural Justice and Job Satisfaction on Organizational Citizenship Behavior; to test and analyze the effect of Organizational Commitment on Organizational Citizenship Behavior; to test and analyze which influence is greater between the direct influence of Procedural Justice and Job Satisfaction on Organizational Citizenship Behavior through Organizational Commitment with or indirect influence. In this study, the research sample will be the population of all employees of PT Patrari Jaya Utama, so the technique used in this study is a census of 65 employees. The analysis tool used is Multiple Linear Regression Analysis and Path Analysis. The results showed that there was a significant influence between Procedural Justice and Job Satisfaction on Organizational Commitment: There was a significant influence between Procedural Justice on Organizational Citizenship Behavior; There is no influence between job satisfaction on Organizational Citizenship Behavior; There is a significant influence between Organizational Commitment to Organizational Citizenship Behavior.